Evaluation of different traits from day-old to age at first eggs of Fayoumi and White leghorn chickens and their reciprocal crossbreeds - Kasaye Assefa Balcha; Yosef Tadesse Mengesha; Ewonetu Kebede Senbeta; Negassi Ameha Zeleke (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This study evaluated the different traits from day-old to age at first eggs of Fayoumi and White leghorn (WLH) F1 chickens and their reciprocal crossbreeds. Materials and Methods: In this study, 1,000 eggs were used to obtain experimental chicks. However, only 150 chicks were selected from each genotype for subsequent trial evaluation and reared on the same diet in a completely randomized design. The effects of genotype on each considered trait were analyzed by the statistical analysis system, and Duncans multiple range test made a significant difference. Results: Comparative evaluations made on all parameters illustrated significant differences (p < 0.05) throughout the study period. F1 acquired from WLH cocks and Fayoumi hens maximized weights almost at all ages during brooding, whereas pure line Fayoumi showed lower importance for the trait stages of growth. Offspring from the crossbreed of WLH cocks and Fayoumi hens had the highest weight gain than any other crossbreeds from 4 to 8 and 12 to 16 weeks of age. Pure line WLH and Fayoumi lay larger eggs and smaller eggs (41.67 and 34.00 g), respectively. The highest and smallest body weight at the age of first egg was 1,364.89 and 1,178.36 g in the main crossbreed and Fayoumi line. The main WLH cock and Fayoumi hens and reciprocal crossbreds advanced in age at first egg by 4 and 11 days, respectively. Conclusion: The leghorn hen and Fayoumi cock crosses could be used to develop potential egg-laying lines than their reciprocal crossbreeds. [J Adv Vet Anim Res 2021; 8(1.000): 1-6]